An Investigation of the Creation of Dialogue-centric Video Games, Using Two Scripting Languages - Hulthén, Felix; Ljungdahl, Axel; Rödström, Gustav; Svensson, Gustav; Tchaefa, Gmal (My University, 2018)
In this report, we investigate the importance of scripting language features used in the development of dialogue-centric video games. This was done by creating two scripting languages, a game engine and a graphical editor; by conducting analyses of features used in existing development tools; and by performing tests in which volunteers used our tools and provided feedback. The analyses and user tests resulted in a set of features which may be important to consider when designing scripting languages for dialogue-centric game development, as well as a number of areas in which we believe future research should be performed.
Keywords: Data- och informationsvetenskap; Computer and Information Science